Characterization of EEG patterns in brain-injured subjects and controls after a Snoezelen® intervention. (November 2016) - Gómez, Carlos; Poza, Jesús; Gutiérrez, María T.; Prada, Esther; Mendoza, Nuria; Hornero, Roberto
Highlights: Snoezelen elicits changes in brain-injured subjects and controls' EEG activity. Our results support the notion that Snoezelen affects the central nervous system. Snoezelen participants are more relaxed after the stimulation. Cognitive deficits of brain-injured subjects may diminish the benefits of Snoezelen. Our study could contribute to design personalized non-pharmacological interventions. Abstract: Background and objective: The aim of this study was to assess the changes induced in electroencephalographic (EEG) activity by a Snoezelen ® intervention on individuals with brain-injury and control subjects. Methods: EEG activity was recorded preceding and following a Snoezelen ® session in 18 people with cerebral palsy (CP), 18 subjects who have sustained traumatic brain-injury (TBI) and 18 controls. EEG data were analyzed by means of spectral and nonlinear measures: median frequency ( MF ), individual alpha frequency ( IAF ), sample entropy ( SampEn ) and Lempel-Ziv complexity ( LZC ). Results: Our results showed decreased values for MF, IAF, SampEn and LZC as a consequence of the therapy. The main changes between pre-stimulation and post-stimulation conditions were found in occipital and parietal brain areas. Additionally, these changes are more widespread in controls than in brain-injured subjects, which can be due to cognitive deficits in TBI and CP groups. Conclusions: Our findings support the notion that Snoezelen ® therapy affects central nervous system, inducing a slowing of oscillatory activity, as well as a decrease of EEG complexity and irregularity. These alterations seem to be related with higher levels of relaxation of the participants.